2006
DOI: 10.1097/01.mpg.0000228105.91240.80
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Pediatric Patients Suffering From Chronic Inflammatory Bowel Disease With and Without Steroid Treatment

Abstract: The prevalence of osteoporosis in pediatric patients with IBD is approximately the same as in adult patients. Osteoporosis is already present before steroid treatment. Data of dual energy x-ray absorptiometry measurements should be transformed into volumetric parameters to compensate for short stature. Otherwise, a lot of growth-stunted patients may be falsely diagnosed as osteopenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 41 publications
5
42
1
4
Order By: Relevance
“…This is supported by the negative correlation between ESR/faecal calprotectin and serum PINP levels in our study and the fact that steroid-naive IBD patients may present with osteoporosis (23,24). Additionally, in active disease other factors such as nutrition or physical inactivity leading to reduced loading of the bones may also contribute to the low PINP levels (25).…”
Section: Discussionsupporting
confidence: 66%
“…This is supported by the negative correlation between ESR/faecal calprotectin and serum PINP levels in our study and the fact that steroid-naive IBD patients may present with osteoporosis (23,24). Additionally, in active disease other factors such as nutrition or physical inactivity leading to reduced loading of the bones may also contribute to the low PINP levels (25).…”
Section: Discussionsupporting
confidence: 66%
“…4A) produce pro-osteoclastogenic cytokines such as TNF (50,51), IL-6 (52, 53), and IL-1 (50,54) and could potentially promote osteoclast differentiation and/or function. As such, OsteoMacs may provide a candidate cellular mechanism to explain why chronic inflammation (55) and systemic infection (56) often result in osteopenia/osteoporosis. Based upon their apposition to bone surfaces and their well-known ability to detect dying cells (57), OsteoMacs are also the most obvious candidates to detect and respond to bone damage (e.g., apoptotic death of osteoblasts and osteocytes), a critical event in initiation of bone remodeling and osteoclast recruitment (58).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies that used DXA have reported reduced BMD measurements for patients with short stature and/or genetic syndromes associated with short stature; this result could be explained by reduced height because BMD is a measurement of area and these patients have reduced height, which negatively affects their BMD values (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 89%